Testing bidirectionality in associations of Awareness of Age-Related gains and losses with physical, mental, and cognitive functioning across 1 year: the role of age - Sabatini, Serena; Wahl, Hans-Werner; Diehl, Manfred; Clare, Linda; Ballard, Clive; Brooker, Helen; Corbett, Anne; Hampshire, Adam; Stephan, Blossom C M (The journals of gerontology. Series B, Psychological sciences, social sciences, 2023)
The bidirectionality between self-perceptions of aging and health-related outcomes may depend on age group. Therefore, we tested such bidirectionality among individuals in late midlife (50-64 years), young-old age (65-74 years), and old-old age (75+ years), taking advantage of the construct of Awareness of Age-Related Change (AARC) and its 2-dimensionality in terms of AARC-gains and AARC-losses. Various conceptualizations of physical, mental, and cognitive functioning were used as outcomes.Data from 2 measurement occasions (2019 and 2020) from the UK PROTECT study for individuals in late midlife (N = 2,385), young-old age (N = 2,430), and old-old age (N = 539) were used. Data on self-reported functional difficulties, depression, anxiety, and performance on four computerized cognitive tasks (i.e., verbal reasoning, paired associate learning, self-ordered search, and digit span) providing a score for verbal reasoning and a score for working memory were analyzed using cross-lagged panel models.Across all 3 age groups, the bidirectional associations of AARC-gains with indicators of functioning were not significant, whereas higher AARC-losses significantly predicted slightly greater functional difficulties and higher depression and anxiety levels. Higher AARC-losses predicted slightly poorer Verbal Reasoning only in old-old age and poorer Working Memory predicted slightly higher AARC-losses only in young-old age. The remaining associations of AARC-losses with cognitive tasks were not statistically significant.In accordance with previous research targeting other indicators of self-perceptions of aging, this study supported a stronger impact of AARC-losses on indicators of physical functioning and mental health than vice versa from midlife to old-old age.
Veröffentlicht: 6 October 2023
Gesehen am 08.01.2024